Preparation And Characterization Of Spherical Agglomerates Of Ketoprofen By Neutralization Method - MUDIT DIXIT; DR. P. K. KULKARNI (International Journal of Pharma and Bio Sciences, 2010)
Ketoprofen, an anti-inflammatory drug, exhibits poor water solubility and flow properties. Spherical agglomerates were prepared by neutralization method. Crystallization medium used for spherical agglomerates of ketoprofen consisted of 1 M Sodium hydroxide; 0.25 M hydrochloric acid; chloroform (bridging liquid) in the ratio of 20:55:25, respectively. Spherical agglomerates were characterized by differential scanning calorimetry, Infrared spectroscopy, X-ray diffractometry and scanning electron microscopy. Micromeritic and dissolution behavior studies were carried out. Process variables such as amount of bridging liquid, stirring time and duration of stirring were optimized. Dissolution profile of the spherical agglomerates was compared with pure sample and recrystallized sample. Tablets were prepared using spherical agglomerates by direct compression and evaluated for tablet properties. Spherical agglomerates exhibited decreased crystallinity and improved micromeritic properties. The dissolution of the spherical agglomerates was improved compared with pure sample. The dissolution profiles of ketoprofen tablets prepared using spherical agglomerates exhibit greater dissolution behaviour than tablets prepared by powder raw material.